EGDT MODIFICATIONS USING IVC DIAMETER AND IVC COLLAPSIBILITY INDEX TO PROVIDE INTRAVASCULAR ADEQUACY FOR SEPSIS MANAGEMENT IN REMOTE AREA - Irawan, Andi; Pradhana, Adinda Putra; Senapathi, Tjokorda Gde Agung (Bali Journal of Anesthesiology, 2018)
Early Goal Directed Therapy (EGDT) protocols can still be considered to provide clear guidelines for bedside clinicians to treat sepsis. The use of EGDT protocol requires Central Venous Catheter (CVC) installation to calculate Central Venous Pressure (CVP). In the field, especially in the remote area, the installation of CVC often cannot be done because of the unavailability of tools or other reasons. Wiryana, et al. found that there was a strong negative correlation between CVP and collapsibility index of Inferior Vena Cava (IVC) and that IVC Collapsibility Index (IVC CI) could replace CVP(1), so it could be used to replace the role of CVP on modified EGDT protocol. Five patients were measured IVC diameter and IVC CI after initial fluid therapy and had an expiratory IVC diameter and a collapsibility index belonging to the CVP group of 11-15cmH2O according to Katja, et al(2).